SEA LEVEL VARIATION AND GEOSTROPHIC CURRENT OF THE SUNDA STRAIT BASED ON TIDAL AND WIND DATA IN YEAR 2008 - Resni Oktavia; John Iskandar Pariwono; Parluhutan Manurung (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2011)
Sea level variation from four tide-gauge data in the Sunda Strait, Indonesia, in the year 2008 has been studied by using Wavelet 1 D Daubechius 1 level 5 type and Fast Fourier Transform methods. The hourly sea level variation in April and November (representing transitional seasonal conditions) is approximately +0.49 m; whereas in January (representing Northwest Monsoon condition) and July (representing Southeast Monsoon condition) can reach up to -0.48 m. In 2008, sea level variation in the Sunda Strait is mainly influenced by the monsoon. Results from this study show that there are at least three phenomena of sea level variations in the Sunda Strait, namely (1) seasonal variation (periodicity between 4-6 months) where it is believed influenced by the Java Sea; (2) intra-seasonal (periodicity between 1-3 months), which is more influenced by the Indian Ocean; and (3) tidal forcing (periodicity between 14-17 days, suggesting fortnightly tidal forces) which propagates from the Indian Ocean into the Sunda Strait. Result from surface geostrophic approximation calculation suggests that during Southeast Monsoon (June-August), monthly mean current flows southwestwardly towards the Indian Ocean with a velocity of 0.14-0.16 m/s. Whereas during Northwest monsoon (December-February), current flows northeastwardly towards the Java Sea with a velocity of 0.14-0.17 m/s. Furthermore, on the daily time scale, tidal current in the Sunda Strait flows into the Java Sea (Indian Ocean) during high tide (low tide) with a velocity ranging from 0.51 to 0.72 m/s (0.48 to 0.51 m/s).Keywords: sea level variation, geostrophic approximation, tides, monsoon, Sunda Strait